Tracking tripartite interaction dynamics: isolation, integration, and influence of bacteriophages in the Paraburkholderia-Dictyostelium discoideum symbiosis system - DiSalvo, Susanne; Maness, Negar; Braun, Andrew; Tran, My; Hofferkamp, Andrew (Frontiers in Microbiology, 2025)
IntroductionBacteriophages influence interactions between bacterial symbionts and their hosts by exerting parasitic pressure on symbiont populations and facilitating bacterial evolution through selection, gene exchange, and prophage integration. Host organisms also modulate phage-bacteria interactions, with host-specific contexts potentially limiting or promoting phage access to bacterial symbionts or driving alternative phenotypic or evolutionary outcomes.MethodsTo better elucidate tripartite phage-bacteria-host interactions in real-time, we expanded the Dictyostelium discoideum-Paraburkholderia symbiosis system to include Paraburkholderia-specific phages. We isolated six environmental Paraburkholderia phages from soil samples using a multi-host enrichment approach. We also identified a functional prophage from monocultures of one of the Paraburkholderia symbiont strains implemented in the enrichment approach. These phages were evaluated across all three amoeba-associated Paraburkholderia symbiont species. Finally, we treated Paraburkholderia infected amoeba lines with select phage isolates and assessed their effects on symbiont prevalence and host fitness.ResultsThe isolated phages exhibited diverse plaquing characteristics and virion morphologies, collectively targeting Paraburkholderia strains belonging to each of the amoeba-symbiotic species. Following amoeba treatment experiments, we observed that phage application in some cases reduced symbiont infection prevalence and alleviated host fitness impacts, while in others, no significant effects were noted. Notably, phages were able to persist within the symbiont-infected amoeba populations over multiple culture transfers, indicating potential long-term interactions.DiscussionThese findings highlight the variability of phage-symbiont interactions within a host environment and underscore the complex nature of phage treatment outcomes. The observed variability lays the foundation for future studies exploring the long-term dynamics of tripartite systems, suggesting potential mechanisms that may shape differential phage treatment outcomes and presenting valuable avenues for future investigation.